Short-Term Forecasting and Detection of Explosions During the 2016–2017 Eruption of Bogoslof Volcano, Alaska - Coombs, Michelle L.; Wech, Aaron G.; Haney, Matthew M.; Lyons, John J.; Schneider, David J.; Schwaiger, Hans F.; Wallace, Kristi L.; Fee, David; Freymueller, Jeff T.; Schaefer, Janet R.; Tepp, Gabrielle (Frontiers in Earth Science, 2018)
We describe a multidisciplinary approach to forecast, rapidly detect, and characterize explosive events during the 2016–2017 eruption of Bogoslof volcano, a back-arc shallow submarine volcano in Alaska’s Aleutian arc. The eruptive sequence began in December 2016 and included over 60 discrete explosive events. Because the volcano has no local monitoring stations, we used distant stations on the nearest volcanoes, Okmok (54 km) and Makushin (72 km), combined with regional infrasound sensors and lightning detection from the Worldwide Lightning Location Network (WWLLN). Monitoring of activity used a combination of scheduled checks combined with automated alarms. Alarms triggered on real-time data included real-time seismic amplitude measurement (RSAM); infrasound from several arrays, the closest being on Okmok; and lightning strokes detected from WWLLN within a 20-km radius of the volcano. During periods of unrest, a multidisciplinary response team of four people fulfilled specific roles to evaluate geophysical and remote-sensing data, event-specific ash-cloud dispersion modeling, interagency coordination, and development and distribution of formalized warning products. Using this approach, for events that produced ash clouds ≥7.5 km above sea level, AVO called emergency response partners 15 minutes, and issued written notices 30 minutes, after event onset (mean times). Factors that affect timeliness of written warnings include event size and number of data streams available; bigger events and more data both decrease uncertainty and allow for faster warnings. In remote areas where airborne ash is the primary hazard, the approach used at Bogoslof is an effective strategy for hazard mitigation.